Corrosion Resistance of Magnesia Binders in Aggressive Liquids - Miryuk Olga (Environmental and Climate Technologies)
The article is devoted to the relevant problem of increasing the durability of magnesia materials. The objective of the work is to study the effect of mineral additives and salt grouting liquid on magnesia binders’ hardening and resistance in aggressive liquid environments. The experiments involved the following starting materials such as: caustic magnesite, metallurgical slag, ash from thermal power plants, and iron ore processing waste. Solutions of magnesium chloride, magnesium sulfate, iron sulfate, and their combinations were used to close magnesia binders. The composition of magnesia binders was studied using diffractometric analysis. Materials’ properties were determined by physical and mechanical testing. There are presented strength tests’ results of magnesia binders kept in various environments such as air, water, and salt solutions. The strength indicators are supplemented by photographs of samples appearance subjected to corrosive effects. The reasons for changes in binders’ resistance in aggressive liquids are substantiated. Preferred compositions of magnesia binders demonstrating the increased resistance to corrosion processes were proposed. The research results are aimed at developing resource-saving technologies and increasing the durability of effective building materials, expanding the scope of application of magnesite materials.